Egr-1 deficiency in bone marrow-derived cells reduces atherosclerotic lesion formation in a hyperlipidaemic mouse model - Albrecht, Claudia; Preusch, Michael; Hofmann, Götz-Ulrich; Morris-Rosenfeld, Samuel; Blessing, Erwin; Rosenfeld, Michael E.; Katus, Hugo; Bea, Florian (Cardiovascular research, 2010)
Early growth response gene-1 (Egr-1) regulates the expression of genes important to cardiovascular disease. Within atherosclerotic lesions, Egr-1 is expressed in smooth muscle cells, endothelial cells, and macrophages. Since macrophages play a pivotal role in atherosclerotic lesion initiation and progression, this study investigated the effects of Egr-1 deficiency within bone marrow-derived cells on the development of atherosclerosis in a hyperlipidaemic mouse model.Bone marrow from Egr-1-deficient mice and wild-type controls was transplanted into lethally irradiated LDL receptor null mice. After 26 weeks on a high fat diet, atherosclerotic lesion size within the aortic sinus of recipients was evaluated. Mice receiving Egr-1-deficient bone marrow had significantly decreased lesion size compared with controls. Lesions of these mice contained fewer macrophages and had reduced expression of vascular cell adhesion molecule-1 (VCAM-1), tissue factor, as well as transforming growth factor receptor type II, which are target genes of Egr-1. These results were validated by in vitro analysis of Egr-1-deficient peritoneal macrophages which, after lipopolysaccharide stimulation, had decreased VCAM-1 and tissue factor mRNA expression compared with wild-type controls.This study demonstrates that bone marrow-derived Egr-1 promotes macrophage accumulation, atherosclerotic lesion development, and lesion complexity.